PENGINTEGRASIAN PENDIDIKAN, KESEHATAN, DAN PENDAPATAN DALAM UPAYA MENINGKATKAN DERAJAT KESEJAHTERAAN MASYARAKAT DI DESA 3T - Dedi Hariyanto; Arif Didik Kurniawan; Devi Yasmin (Universitas Muhammadiyah Pontianak, 2017)
Empaci village was underdeveloped particularly in education, public health, and economic sector. As a deprived area, support on those particular sectors were needed. Few integrated programs in education, health, and economy has been implemented to promote resident welfare. The programs started by recruiting students to play an active role to manage the programs. Most of the programs empowered local people by means of participative and communicative approach. The programs has been very successful in which it was fully supported by local government. As a result, new local public bodies have been formed including volunteer to remove illiteracy and posyandu cadres. In addition, medicinal herbal garden (toga) and commercial fishery was also erected to improve resident income. We also taught the locals to creat their own fish food from local materials. Keywords: people empowerment, Empaci village, 3T, integrated programs